ダイ 1 カイ コクサイ ペンギン カイギ ホウコク ペンギン ケンキュウ ノ ドウコウ - 青柳, 昌宏; アオヤナギ, マサヒロ; 上田, 一生; ウエダ, カズオキ; Aoyanagi, Masahiro; Ueda, Kazuoki (1989)
P(論文) 第1回国際ペンギン会議が, 1988年8月, ニュージーランド, オタゴ大学で開催された。123名が参加し, 口頭発表, 展示発表合わせて53の論文が提出された。アデリーペンギン属, エンペラーペンギン属の5種のペンギンの発表論文が, そのうち22を占め, これらのペンギンが主たる研究対象となっていることを示していた。海中におけるペンギンの行動研究の手段として, 深度計, 電波による追跡装置が関心の的であった。これらの装置を用いて, 採餌, エネルギーの移動の研究が進められている。ロス海における, アデリーペンギンの長期個体数変動調査の結果が, 南極海洋生態系を知る手掛かりとなるものとして評価された。ニュージーランドに生息するキガシラペンギンの個体数減少が報告された。 The First International Conference on Penguins was held in Dunedin, New Zealand, from 16 to 19 August 1988. Hosted by John DARBY of Otago Museum and Lloyd DAVIS of the University of Otago, the conference was attended by 123 penguin students representing ten countries. After the keynote address by Bernard STONEHOUSE, 53 papers presented at the conference focused on nearly all aspects of penguin biology. Attention was paid mainly to the 5 species of Pygoscelis and Aptenodytes and 22 papers were devoted to these species. Depth recorders and radiotracking systems were intensively employed in relation to the behavioral researches of penguins in the sea. It was expected that the application of newly developed instruments would benefit such researches as foraging and energetics of penguins. The results on the fluctuation in Adelie penguin populations in the Ross Sea region, in particular at Cape Bird, Ross Island, were considered as valuable data to understand the structure of Antarctic ecosystems. Serious depletion in population of the yellow-eyed penguin, Megadyptes antipodes, in New Zealand was reported. departmental bulletin paper